Materials in mechanical extremes : fundamentals and applications - Bourne, Neil, 1964- (Cambridge ; New York : Cambridge University Press, 2013)
"This unified guide brings together the underlying principles, and predictable material responses, that connect metals, polymers, brittle solids and energetic materials as they respond to extreme external stresses. Previously disparate scientific principles, concepts and terminology are combined within a single theoretical framework, across different materials and scales, to provide all the tools necessary to understand, and calculate, the responses of materials and structures to extreme static and dynamic loading. Real-world examples illustrate how material behaviours produce a component response, enabling recognition - and avoidance - of the deformation mechanisms that contribute to mechanical failure. A final synoptic chapter presents a case study of extreme conditions brought about by the infamous Chicxulub impact event. Bringing together simple concepts from diverse fields into a single, accessible, rigorous text, this is an indispensable reference for all researchers and practitioners in materials science, mechanical engineering, physics, physical chemistry and geophysics"--
1. Natural Extremes -- 2. A basic analytical framework -- 3. Platforms to excite a response -- 4. Tools to monitor response -- 5. Metals -- 6. Brittle materials -- 7. Polymers -- 8. Energetic materials -- 9. Asteroid impact.
engineering bookfair2016
Includes bibliographical references and index.
Keywords: Materials -- Mechanical properties; Mechanics, Applied